Dynamic Inefficiencies in Insurance Markets: Evidence from Long-Term Care Insurance - Finkelstein, Amy; McGarry, Kathleen; Sufi, Amir (American Economic Review, 2005)
Dynamic Inefficiencies in Insurance Markets: Evidence from Long-Term Care Insurance by Amy Finkelstein, Kathleen McGarry and Amir Sufi. Published in volume 95, issue 2, pages 224-228 of American Economic Review, May 2005